2021
DOI: 10.2147/jir.s337737
|View full text |Cite
|
Sign up to set email alerts
|

The Inverted-U Relationship Between Dietary Inflammatory Potential and Hearing Loss Among Adults Aged 20 Years and Over in the United States: A Cross-Sectional Study

Abstract: Purpose:The purpose of this study was to examine the relationship between dietary inflammatory index and objective hearing loss (HL). Materials and Methods: A cross-sectional analysis of a nationally representative sample of participants was performed based on data in National Health and Nutrition Examination Survey (NHANES) (2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016). HL was defined as pure tone averages >25 dB at 500, 1000, and 2000 Hz (low frequency); 3000, 4000, 6000, and 8000 Hz (high frequency) in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…Several previous studies have suggested that healthy diets were related with lower risk of hearing loss [7,8,19,20], which is consistent with results from the present study. However, prior investigators have often concentrated on nutrients, foods, or dietary habits.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Several previous studies have suggested that healthy diets were related with lower risk of hearing loss [7,8,19,20], which is consistent with results from the present study. However, prior investigators have often concentrated on nutrients, foods, or dietary habits.…”
Section: Discussionsupporting
confidence: 93%
“…In several observational studies, antioxidants or antiinflammatory dietary patterns [19,20] have been found to be inversely related to hearing loss. UPF might be linked to age-related hearing loss in this sense, because the association between UPFs and inflammatory activity has been reported in several studies [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Available food parameters for DII calculating included: vitamins A, B1, B2, B6, B12, C, and E; carbohydrates; alcohol; caffeine; fiber; saturated fatty acids; monounsaturated fatty acids; polyunsaturated fatty acids; cholesterol; omega‐3 fatty acids; omega‐6 fatty acids; niacin; beta‐carotene; iron; magnesium; folic acid; zinc; selenium; protein; total fat; and energy. To minimize the effect of total energy intake, the DII was calculated per 1000 kcal of food consumed (E‐DII) (Fu et al., 2021 ; Huang et al., 2022 ). The final E‐DII is a continuous score, with higher values indicating more pro‐inflammatory diets.…”
Section: Methodsmentioning
confidence: 99%